Types of diversity and ecological functions of pteridophytes in the Lawe Secepit Waterfall Kendal - Ulfah, Maria; Santoso, Luhur Pujo; Alamsyah, Ricky; Setyaningrum, Sulis; Kurniawati, Septiana (Biogenesis: Jurnal Ilmiah Biologi, 2023)
.